KANO STATE’S EDUCATIONAL SECTOR: SUCCESSES AND CHALLENGES AMID STATE OF EMERGENCY (Wudil Journal of Science and Technology Education, 2025)
Education remains a vital engine of economic growth and national development. In Kano State,persistent educational decline led to the declaration of a State of Emergency on Education toaddress systemic deficiencies. This study critically examines the successes and challengesrecorded in the education sector following this intervention. The study adopted a descriptivesurvey design using both qualitative and quantitative methods. Data were collected from 150respondents comprising teachers, school administrators, and Ministry of Education officials.Descriptive statistics such as frequencies, percentages, and charts were used to analyze the data.Results revealed significant achievements, including school rehabilitation, improved enrollment,and increased teacher recruitment. However, challenges such as inadequate funding, poorinfrastructure, insecurity, and socio-cultural barriers continue to impede progress. The studyconcludes that while notable strides have been made, the sustainability of reforms depends onconsistent funding, accountability, and strong community participation.
Keywords: Education, Kano State, Policy Reform, State of Emergency, Challenges, Development